Impact of COVID 19 on Health Care Personnel (Indian Journal of Public Health Research & Development, 2020)
The outbreak of COVID 19 is highly challenging for the frontline worker that is health care personnel.This novel virus originated from Wuhan China, December 2020, as this deadly virus is highly contagious itaffected all globally. WHO declared pandemic on March 2020, and also published guidelines to be followedby the HCP while providing patient care. HCP face multiples issues continuously which develop whileproviding patient care such as occupational burnout due to shortage of manpower. HCP also faced physicaland psychological violence during delivering patient care which is again too stressful. Many HCP worksovertime of 12 to 13 hrs due to shortage of manpower and also many patients got admitted daily. Thosehealth workers who got contacted without proper PPE, they used to keep quarantine. Due to this HCP arekept separation from family members and this is again stressful for the concern person especially lady HCPhaving small children at home. Apart from these many issues, HCP also faced imbalance nutrition, deprivesleeping pattern, racism issues especially to north east Indian HCP, transports issue due to lock down, lackof PPE, impaired coping mechanism with children.
Keywords: HCP, WHO, PPE, COVID 19, Stress, burn out